EMERGING THERAPY FOR DENGUE - R., Tayade M.; M., Shinkar D.; B., Patil P.; B., Saudagar R. (International Journal of Current Pharmaceutical Research, 2018)
Dengue fever is acute febrile diseases, it's caused by one of four closely related virus serotypes of the genusare Flavivirus, family Flaviviridae. Each serotype is sufficiently different that there is no cross-protection and epidemics caused by multiple serotypes can occurs. It's transmitted to humans by the mosquito. The incidence of dengue has grown around the world in recent a period of ten years. However, several classes of agents are in under investigation as potential anti-dengue drugs, including direct host modulators, antivirals, and RNAi therapeutics. These anti-dengue drugs in development will be reviewed here.